Analysis of the Influence of the Efficiency of the Implementation of the Queue System in Improving the Quality of Administrative Services At the Hulonthalangi Health Center - Anak Agung Reduari; Herlina Jusuf; Ulfa Aulia; Sarinah Basri K; Tri Septian Maksum (Universitas Muhammadiyah Palu, 2026)
The implementation of a good queue system can help manage the flow of services so that waiting time can be minimized and the service process becomes more orderly and efficient. This study aims to analyze the effect of the efficiency of the implementation of the queue system on the quality of administrative services at the Hulonthalangi Health Center. Type of quantitative research, analytical survey research method with cross sectional approach. The research population of all patients who performed administrative services at the Hulonthalangi Health Center in November was 867 patients. The number of samples using the Lemeshow formula was 236 respondents. The sampling technique in this study uses accidental sampling techniques. Data analysis was conducted using a Simple Linear Regression test. Based on the results of data analysis, a p-value = 0.000 (P<0.05) was obtained, so there was an influence between the implementation of the queue system and the quality of administrative services at the Hulonthalangi Health Center. The correlation coefficient value (R) of 0.897 shows a very strong influence, while the determination coefficient value (R²) of 0.805 shows that the implementation of the queue system contributes 80.5% to the quality of administrative services. In conclusion, the implementation of the queue system can have a positive effect on the quality of administrative services at the Hulonthalalangi Health Center. Suggestion to the Puskesmas to continue to improve the management of the queue system so that administrative services to patients become more efficient.